Les Français de Londres, pas tous expatriés - Diane Le Luyer (EchoGéo)
The international presence embodied by French nationals living abroad is an asset for France. Underlying the measures deployed for them, the objectives of influence pursued by the nation-state sometimes compete with the objectives of support for the population. Designed from a modern and universalist perspective, the public policies are based on a valuable image of the population established abroad that can be used to capitalise on the pursuit of a soft power agenda. French emigration in London, once aristocratic or bourgeois, has become more democratic, and the social recomposition of expatriation, which reflects in professional careers, reveals the failure of institutional mechanisms to fulfill their mission of providing an inclusive support system for citizens.